Modeling Circular Economy Behavior: The Influence of Brand Activism and Environmental Awareness on Green Repurchase Intention - Muksalmina Muksalmina; Salwa Hayati Hasan; Ahmad Syahyana (Indatu Journal of Management and Accounting, 2026)
This study investigates the influence of Brand Activism and Environmental Awareness on Green Repurchase Intention, with Circular Economy Behavior as a mediating variable. The study addresses the persistent attitude–behavior gap in sustainable consumption, whereby consumers often express environmental concern but do not consistently engage in green repurchasing behavior. A quantitative associative approach was employed using data collected from consumers in Banda Aceh City and Aceh Besar Regency, Indonesia, through structured questionnaires. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that Brand Activism and Environmental Awareness positively and significantly influence Circular Economy Behavior. Circular Economy Behavior also demonstrates the strongest positive effect on Green Repurchase Intention, emerging as the most dominant predictor in the model. In addition, Brand Activism directly and positively affects Green Repurchase Intention, whereas Environmental Awareness shows a negative but significant direct effect, indicating that environmental awareness alone does not necessarily encourage repeated green purchasing. The mediation analysis further reveals that Circular Economy Behavior acts as an important behavioral pathway linking environmental values and brand-related factors with sustainable repurchase behavior. The indirect effects also indicate that Circular Economy Behavior strengthens the influence of Brand Activism and Environmental Awareness on Green Repurchase Intention by translating environmental values and brand-related stimuli into consistent sustainable consumption practices. These findings suggest that sustainable repurchase behavior is primarily shaped by actual behavioral engagement rather than cognitive awareness alone. This study contributes to the sustainable consumer behavior literature by emphasizing the role of Circular Economy Behavior as a key mediating mechanism within the circular economy framework. The findings also suggest that companies and policymakers should focus on encouraging sustainable behavioral practices rather than relying solely on environmental awareness campaigns.